Aortic coarctation a systemic vessel disease: insights from magnetic resonance imaging - Eichhorn, Joachim; Ley, Sebastian; Kropp, Florian; Fink, Christian; Brockmeier, Konrad; Loukanov, Tsvetomir; Ley-Zaporozhan, Julia (The thoracic and cardiovascular surgeon, 2019)
Even after successful aortic coarctation (CoA) repair, hypertension causes premature morbidity and mortality. The mechanisms are not clear. The aim was to evaluate elastic wall properties and aortic morphology and to correlate these results with severity of restenosis, hypertension, aortic arch geometry, noninvasive pressure gradients, and time and kind of surgical procedure.
Gesehen am 03.12.2019